Find the best solutions to your questions at Westonci.ca, the premier Q&A platform with a community of knowledgeable experts. Get the answers you need quickly and accurately from a dedicated community of experts on our Q&A platform. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.
Sagot :
To solve the quadratic equation [tex]\(3x^2 - 2x + 4 = 0\)[/tex], we will use the quadratic formula:
[tex]\[ x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \][/tex]
Here, the coefficients are [tex]\(a = 3\)[/tex], [tex]\(b = -2\)[/tex], and [tex]\(c = 4\)[/tex].
1. Calculate the discriminant:
[tex]\[ \Delta = b^2 - 4ac \][/tex]
[tex]\[ \Delta = (-2)^2 - 4 \cdot 3 \cdot 4 \][/tex]
[tex]\[ \Delta = 4 - 48 \][/tex]
[tex]\[ \Delta = -44 \][/tex]
Since the discriminant [tex]\(\Delta\)[/tex] is negative, this indicates that the roots are complex.
2. Find the roots using the quadratic formula:
[tex]\[ x = \frac{-(-2) \pm \sqrt{-44}}{2 \cdot 3} \][/tex]
[tex]\[ x = \frac{2 \pm \sqrt{-44}}{6} \][/tex]
We know that [tex]\(\sqrt{-44} = \sqrt{44} \cdot i\)[/tex].
[tex]\[ x = \frac{2 \pm \sqrt{44} \cdot i}{6} \][/tex]
Simplify the square root of 44:
[tex]\[ \sqrt{44} = \sqrt{4 \cdot 11} = 2 \sqrt{11} \][/tex]
Substituting this in:
[tex]\[ x = \frac{2 \pm 2 \sqrt{11} \cdot i}{6} \][/tex]
Divide the numerator and denominator by 2:
[tex]\[ x = \frac{1 \pm \sqrt{11} \cdot i}{3} \][/tex]
Thus, the solutions to the equation [tex]\(3x^2 - 2x + 4 = 0\)[/tex] are:
[tex]\[ x = \frac{1 \pm i\sqrt{11}}{3} \][/tex]
Therefore, the correct option is:
B. [tex]\(x = \frac{1 \pm i\sqrt{11}}{3}\)[/tex]
[tex]\[ x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \][/tex]
Here, the coefficients are [tex]\(a = 3\)[/tex], [tex]\(b = -2\)[/tex], and [tex]\(c = 4\)[/tex].
1. Calculate the discriminant:
[tex]\[ \Delta = b^2 - 4ac \][/tex]
[tex]\[ \Delta = (-2)^2 - 4 \cdot 3 \cdot 4 \][/tex]
[tex]\[ \Delta = 4 - 48 \][/tex]
[tex]\[ \Delta = -44 \][/tex]
Since the discriminant [tex]\(\Delta\)[/tex] is negative, this indicates that the roots are complex.
2. Find the roots using the quadratic formula:
[tex]\[ x = \frac{-(-2) \pm \sqrt{-44}}{2 \cdot 3} \][/tex]
[tex]\[ x = \frac{2 \pm \sqrt{-44}}{6} \][/tex]
We know that [tex]\(\sqrt{-44} = \sqrt{44} \cdot i\)[/tex].
[tex]\[ x = \frac{2 \pm \sqrt{44} \cdot i}{6} \][/tex]
Simplify the square root of 44:
[tex]\[ \sqrt{44} = \sqrt{4 \cdot 11} = 2 \sqrt{11} \][/tex]
Substituting this in:
[tex]\[ x = \frac{2 \pm 2 \sqrt{11} \cdot i}{6} \][/tex]
Divide the numerator and denominator by 2:
[tex]\[ x = \frac{1 \pm \sqrt{11} \cdot i}{3} \][/tex]
Thus, the solutions to the equation [tex]\(3x^2 - 2x + 4 = 0\)[/tex] are:
[tex]\[ x = \frac{1 \pm i\sqrt{11}}{3} \][/tex]
Therefore, the correct option is:
B. [tex]\(x = \frac{1 \pm i\sqrt{11}}{3}\)[/tex]
Thank you for choosing our service. We're dedicated to providing the best answers for all your questions. Visit us again. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Westonci.ca is here to provide the answers you seek. Return often for more expert solutions.